THE INFLUENCE OF FAMILY PSYCHOLOGY AND GENDER STEREOTYPES ON THE FORMATION OF STUDENTS' PROFESSIONAL MOTIVES (Universal International Scientific Journal, 2026)
This article analyzes the influence of family psychology and gender stereotypes on the formation of students' professional motivations. The study examined the role of family environment, parental views, social stereotypes, and gender-related ideas in the process of students' career choice. The results of the study, conducted on the basis of scientific literature analysis, observation, and questionnaire methods, show that psychological support in the family and stereotype-free upbringing are important factors in the formation of students' professional motivation. The article also substantiates the importance of cooperation between educational institutions and families in the process of career choice
Keywords: family psychology; gender stereotypes; professional motivation